An exploration study to detect important factors influencing on development of RFID in after sales services - Gholamreza Hashemzadeh; Ali Namkin; Mohammad Hassani (Management Science Letters)
Radio-frequency identification (RFID) is the wireless use of electromagnetic fields to transfer necessary information, for the purposes of automatically identifying and tracking tags attached to various objects. This paper presents a survey to study the role of different factors influencing on RFID implementation in after sales services in auto industry. The study designs a questionnaire and distributes it among 20 managers who work for after sales services in auto industry located in city of Tehran, Iran. Cronbach alpha has been calculated as 0.74, which is well above the minimum acceptable level. Using the existing literature as well as a survey with experts, the study has detected four important factors including management, technical, economic and environmental factors. We also weight all factors and sub-factors using Shannon entropy method.